PENINGKATAN KONDISI FISIK MELALUI PEMBELAJARAN SENAM PUTRI ANGGOTA UNIT KEGIATAN MAHASISWA AEROBIK UNIVERSITAS NADHLATUL ULAMA SURABAYA - Sunanto, Sunanto; Mariati, Pance; Rusdiyanto, Nurholis (Universitas Islam Balitar, 2019)
This research aims at investigating the improvement of physical condition of members of Student Activity Unit (UKM) of women aerobic gym in Universitas Nahdhlatul Ulama Surabaya (UNUSA) through aerobic gym learning. This research adopted quantitative approach through descriptive method to describe physical condition of UKM members of women aerobic gym that included: endurance of heart muscle, arm muscle, and stomach muscle, and flexibility. Sample of this study engaged 20 students of women aerobic gym of UNUSA. Results revealed that90% of the students had very low heart muscle endurance. 80% of the students had low arm muscle endurance, whereas 20% of the students’ arm muscle endurance was very low. 65% of the students had adequate stomach muscle endurance, while 35% of the students had low stomach muscle endurance. 40% of the students had low flexibility, while 60% of the students had very low flexibility. Aerobic gym learning needs to be done gradually and well programmed by following frequency standard, intensity, and training tempo. To achieve a good physical condition, portion of physical training must suit the possessed skills.